2021
DOI: 10.1111/imj.14881
|View full text |Cite
|
Sign up to set email alerts
|

Energy drinks: a narrative review of their physiological and pathological effects

Abstract: The consumption of energy drinks (Edks) has increased significantly in past years, with a growing market that is estimated to reach $61 billion by 2021 worldwide. Several studies demonstrated the physiological and pathological effects of these substances contained in Edks. The most common ingredient contained in Edks is caffeine, which is commonly mixed with taurine, and B-group vitamins. Scientific evidence of potentially serious adverse health effects are known, but it would be better to acquire more informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 56 publications
(108 reference statements)
0
16
0
5
Order By: Relevance
“…According to various reports, EDs can cause all kinds of arrhythmias, with occurring atrial fibrillation (AF) the most often [ 61 ]. QT prolongation, aortic dissection, myocardial infarctions, acute coronary vasospasm, and sudden death have been also observed in healthy subjects with structurally normal hearts or high-risk cardiovascular patients due to massive quantities of EDs consumption [ 62 , 63 , 64 ]. As a long-term effect, EDs are able to induce morphological changes in the heart muscle.…”
Section: Alarming Effects Associated With Energy Drink Consumptionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to various reports, EDs can cause all kinds of arrhythmias, with occurring atrial fibrillation (AF) the most often [ 61 ]. QT prolongation, aortic dissection, myocardial infarctions, acute coronary vasospasm, and sudden death have been also observed in healthy subjects with structurally normal hearts or high-risk cardiovascular patients due to massive quantities of EDs consumption [ 62 , 63 , 64 ]. As a long-term effect, EDs are able to induce morphological changes in the heart muscle.…”
Section: Alarming Effects Associated With Energy Drink Consumptionmentioning
confidence: 99%
“…In addition, a recent study on 129,809 Korean adolescents presented that frequent ED consumption was associated with allergic diseases, such as asthma, allergic rhinitis, and atopic dermatitis [ 73 ]. The last finding also demonstrated that EDs containing caffeine can stimulate gastrin and gastric acid secretion and may reduce the competence of the lower esophageal sphincter, which eventually leads to gastroesophageal reflux disease (GERD) [ 64 , 73 ]. Interestingly, a case study revealed that atrophic gastritis and the gastric intestinal metaplasia can be limited with the withdrawal of EDs [ 74 ].…”
Section: Alarming Effects Associated With Energy Drink Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the most comprehensive review as other reviews are only driven by case reports or have not captured the totality of available literature ( 69 , 70 ). However, several limitations should be noted when interpreting our findings in this review.…”
Section: Discussionmentioning
confidence: 99%